Protective role of salt in catalysis and maintaining structure of halophilic proteins against denaturation - Sinha, Rajeshwari; Khare, Sunil K. (Frontiers in Microbiology, 2014)
Search for new enzymes of industrial relevance, bestowed with novel properties continues to be a desirable pursuit in enzyme research. "Halophilism" is the unusual existence of life in saline/ hypersaline habitats and “haloenzymes”, are the proteins from such origin, naturally endowed with unique structural features which enable them to sustain functionality under high salt. Driven by industrial requirements, halophilic enzymes have been explored for their stability and catalytic abilities under harsh operational conditions. These have been documented to withstand high temperature, pH, organic solvents, and chaotropic agents. However, this stability is modulated by salt. Understanding the basis of salt mediated protection amidst a denaturing milieu will add significantly to the existing knowledge about structure function relationships in halophilic proteins. Exploring their protein architecture may provide template for rationale design of stable enzymes. The article encompasses the current level of understanding about haloadaptations in halophiles and structural basis of their stability against classical denaturants.